KNOWLEDGE, ATTITUDE AND BEHAVIOR FOR USING MASKS AND HAND WASHING DURING PANDEMIC COVID-19 - Emdat Suprayitno; Rendi Editya Darmawan; Nailiy Huzaimah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2021)
Corona Virus Disease-19 or Covid-19 is becoming a pandemic, a global health threat, and a public health emergency that is of international concern, especially in Indonesia. Knowledge, attitude, and preventive measures are important in breaking the chain of COVID-19 transmission. The purpose of the research is to know the knowledge, attitudes, and behavior of Madurese in using masks and handwashing in preventing COVID-19 transmission. This research is a descriptive type, with a cross-sectional survey approach in Madura people in Indonesia. Data collection was conducted using an online questionnaire. The number of people who responded to questions was 282 people. Data is descriptively analyzed by calculating frequency, percentage, and cross-tabulation. Data analysis was performed with a univariate analysis.The results of the study obtained the level of knowledge of Madurese towards the use of masks and handwashing in the prevention of COVID-19 transmission which is 97.2% as much as 271 respondents with good category, attitude 99.6 as many as 281 respondents with positive category, behavior 76% as many as 214 respondents with a good category. It can be concluded that the knowledge, attitudes, and behaviors of madurese in using masks and handwashing in preventing COVID-19 transmission fall into the good category.